Ecotoxicity of nanoscale zero-valent iron particles â€" a review - JosÃ© TomÃ¡s Albergaria; Henri P.A. Nouws; Cristina Maria Delerue-Matos (Fundação Oswaldo Cruz (FIOCRUZ), 2013)
The use of nanoscale zero-valent iron particles (nZVIs) in the environmental remediation of water and soil is increasing. This increase is related to the higher reactivity and mobility of nZVIs compared with that of macro- or micro-sized iron particles. The introduction of nZVIs into the environment raises concerns related to their fate and effect on aquatic and terrestrial biota. Knowledge of these issues will allow a better understanding not only of the remediation process but also of the long-term effects and impact of nZVIs on ecosystems, leading to a safer and more efficient application of these particles. This paper presents the current state of play concerning the toxic effects of nZVIs on organisms at different stages of the food chain. The majority of studies show that nZVIs have a negative impact on bacteria, aquatic invertebrates, such as Daphnia magna, terrestrial organisms, such as Eisenia fetida, and seed germination. However, the number of published studies related to this issue is clearly insufficient. This reinforces the need for further research in order to specify the toxic concentrations of nZVIs that affect the most important target organisms. Furthermore, an evaluation of the effects of the coating of nanoparticles should also be pursued.